Playing the Beethoven piano sonatas - Taub, Robert (New York Amadeus Press, 2009)
Acclaimed pianist Robert Taub offers the insights of a passionate musician who performs all 32 of Beethoven's well-loved piano sonatas in concert worldwide, bringing a "fresh perspective on Beethoven," as the New York Times put it. In this book, he shares his intimate understanding of these works with listeners and players alike.